Mechanisms of Action of Hypomethylating Agents: Endogenous Retroelements at the Epicenter - Kordella, Chryssoula; Lamprianidou, Eleftheria; Kotsianidis, Ioannis (Frontiers in Oncology, 2021)
Abnormal DNA methylation patterns are thought to drive the pathobiology of high risk myelodysplastic syndromes (HR-MDS) and acute myeloid leukemia (AML). Sixteen years after their initial approval the hypomethylating agents (HMAs) 5-azacytidine and 5-aza-2’-deoxycytidine remain the mainstay of treatment for HR-MDS and AML. However, a connection of the hypomethylating or additional effects of HMAs with clinical responses is yet to shown and the mode of action of HMAs remains obscure. Given the relatively short-lived responses and the inevitable development of resistance in HMAs, thorough understanding of the antineoplastic mechanisms employed by HMAs holds critical importance. Recent data in cancer cell lines demonstrate that reactivation of endogenous retroelements (EREs) and induction of a cell-intrinsic antiviral response triggered by RNA neotranscripts may underlie the antitumor activity of HMAs. However, data on primary CD34+ cells derived from HR-MDS patients failed to confirm a link between HMA-mediated ERE modulation and clinical response. Though difficult to reconcile the apparent discrepancy, it is possible that HMAs mediate their effects in more advanced levels of differentiation where cells become responsive to interferon, whereas inter-individual variations in the process of RNA editing and in particular of the ADAR1/OAS/RNase L pathway may also confound the associations of clinical response with the induction of viral mimicry. Further ex vivo studies along with clinical correlations in well annotated patient cohorts are warranted to decipher the role of ERE derepression in the antineoplastic mechanisms of HMAs.